(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Although many causes of malnutrition are discussed in previous studies, the impact of mother schooling on malnutrition among children of rural-urban Pakistan and mediating factors is not posited in case of Pakistan. Hence, this study examine the effect of mother schooling and intervening linkages on acute and chronic malnutrition. Methods: The prior empirical relationship is examined by calculating adjusted risk-ratio with the help of binary logistic regression analyses using a sample size of 3184 rural-urban mothers retrieved from the latest Pakistan Demographic and Health Survey 2012-13 (PDHS). Results: The urban mothers without education are more likely to have stunted and underweighted infants as compared to rural ones. Rural (urban) mothers with poor (moderate) economic position have more chances of having stunted infants than urban (rural) mothers. However, only urban mothers with poor status have more chances of having underweight kids relative to mothers with rich class. The rural mothers with empowerment and with seeking for medical services are less likelihood to have stunted infants than urban ones. Value of the Study: The impact of mediating factors arising from education on rural infants’ health is higher than that on urban infants